“Post-lockdown Depression”: Adaptation Difficulties, Depressive Symptoms, and the Role of Positive Solitude When Returning to Routine After the Lifting of Nation-Wide COVID-19 Social Restrictions - Keisari, Shoshi; Palgi, Yuval; Ring, Lia; Folkman, Adi; Ben-David, Boaz M. (Frontiers in Psychiatry, 2022)
Objectives: The aim of the current study was to identify difficulties in adapting to normal life once COVID-19 lockdown has been lifted. Israel was used as a case study, as COVID-19 social restrictions, including a nation-wide lockdown, were lifted almost completely by mid-April 2021, following a large-scale vaccination operation. Methods: A sample of 293 mid-age and older Israeli adults (M age=61.6±12.8, range 40-85 years old) reported on return-to-routine adaptation difficulties (on a novel index), depression, positive solitude, and several demographic factors. Results: Of the participants, 40.4% met the criteria of (at least) mild depressive symptoms. Higher levels of adaptation difficulties were related to higher ratios of clinical depressive symptoms. This link was moderated by positive solitude. Namely, the association between return-to-routine adaptation difficulties and depression was mainly indicated for individuals with low positive solitude. Conclusions: The current findings are of special interest to public welfare, as adaptation difficulties were associated with higher chance for clinical depressive symptoms, while positive solitude was found to be as an efficient moderator during this period. The large proportion of depressive symptoms that persist despite lifting of social restrictions should be taken into consideration by policy makers when designing return-to-routine plans.